Pendidikan Kesehatan tentang Peran Ibu dalam Deteksi Dini Stunting di Wilayah Kerja Puskesmas Simpang Kawat Kota Jambi - Gustina Gustina (Jurnal Abdimas Kesehatan (JAK), 2021)
The problem of stunting (stunting) is one of the nutritional problems faced in the world, especially in poor and developing countries). Stunting is a problem because it is associated with an increased risk of illness and death, suboptimal brain development, resulting in delayed motor development and stunted mental growth. These nutritional problems can be overcome when they understand the problem and know how to solve it according to their respective conditions (Ramayulis et al, 2018).Target and Outcome: Increased role of mothers with under-five children in early detection of stunting, which aims to reduce the incidence of stunting in under-five.Method of implementation: Administrative preparation, socialization, implementation of health education and evaluation. Activities were carried out from September 2019 to January 2020 by providing education to mothers about the role of mothers in early detection of stunting. Evaluation is done by looking at the results of the pre-test and post-test scores for the mother. Located at Posyandu Lebak Bandung, the Work Area of the Simpang Kawat Puskesmas, Jambi City.Results: After preparation, socialization, implementation and evaluation of the results of the pre-test and post-test scores before health education was carried out on early detection of stunting, out of 15 respondents the role of mother was Poor 9 (60%), Enough 6 (40%), and Good 0 (0%). After health education was carried out about early detection of stunting, from 15 respondents the role of mother was Poor 0 (0%), Enough 4 (26.6%), and Good 11 (73.3%).Conclusion: There was increased knowledge of mothers before and after health education on early detection of stunting. Suggestion: For mothers to always increase knowledge about motherhood through electronic media